2015
DOI: 10.1093/femsec/fiv057
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of biofilm-forming Wrinkly Spreaders in static microcosms and drip-fed columns selects for subtle differences in wrinkleality and fitness

Abstract: Experimental evolution studies are used to investigate bacterial adaptive radiation in simple microcosms. In the case of the Wrinkly Spreader, a class of biofilm-forming adaptive mutants of Pseudomonas fluorescens SBW25, the current paradigm is that they are only evolutionarily successful in static microcosms where they outcompete other lineages for O2 at the air-liquid interface. However, we have isolated Wrinkly Spreaders from drip-fed glass bead columns as an example of parallel evolution. These mutants are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 41 publications
2
33
1
Order By: Relevance
“…These environmental conditions include abiotic factors, which have been shown to influence the phenotypic responses of biofilm dispersal isolates. For example, the fitness exhibited by P. fluorescens with wrinkle colony morphologies vaired depending on if grown in environmenally homogenous or heterogenous microcosms (Udall et al, ). However what is less understood is the influence of competing community members toward the development of heretible trait variation on microbial populations.…”
Section: Introductionmentioning
confidence: 99%
“…These environmental conditions include abiotic factors, which have been shown to influence the phenotypic responses of biofilm dispersal isolates. For example, the fitness exhibited by P. fluorescens with wrinkle colony morphologies vaired depending on if grown in environmenally homogenous or heterogenous microcosms (Udall et al, ). However what is less understood is the influence of competing community members toward the development of heretible trait variation on microbial populations.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that the spatial structure of biofilms has a major impact on competition and cooperation among microbes and drives evolutionary changes within microbial communities (reviewed in refs 4, 5). One particularly well-studied example used static cultures of Pseudomonas fluorescens , where an oxygen gradient led to the emergence of a new wrinkly (W) phenotype that secretes polysaccharides and forms a biofilm at the air–liquid interface67. Interestingly, biofilms formed by W undergo a premature collapse caused by the incorporation of another phenotype into the biofilm without sharing the metabolic costs of exopolymer production8.…”
mentioning
confidence: 99%
“…However, Wrinkly Spreaders may also have a maximal population size; as Wrinkly Spreader numbers grow in the maturing biofilm, only the top ~300  µ m layer of the biofilm remains O 2 -rich and lower regions of the biofilm become increasingly O 2 -limited [11]. In this situation, Wrinkly Spreaders start to compete with one another within the biofilm itself, with different WS mutants showing substantial morphological, metabolic, and fitness variation [17, 3133]. …”
Section: Resultsmentioning
confidence: 99%